2003
DOI: 10.1046/j.1442-200x.2003.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trp64Arg mutation of the β3‐adrenergic receptor gene and C161T substitution of the peroxisome proliferator activated receptor γ gene on obesity in Japanese children

Abstract: All of these data suggest that Trp64Arg mutation of the beta3-AR gene might affect obesity and HDL metabolism in obese boys. In contrast, C161T mutation of the PPARgamma gene, by itself, is unlikely to influence obesity, lipid metabolism or plasma leptin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
2
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
1
24
2
4
Order By: Relevance
“…In humans, the beta-3 adrenergic receptor is predominantly expressed in visceral adipose tissue (Krief et al, 1993). Notably, the Arg allele of this SNP has been linked with increased BMI, adiposity and obesity in children (Arashiro et al, 2003;Endo et al, 2000;Erhardt et al, 2005;Ochoa et al, 2004;Park et al, 2005) supporting the evidence in adults Pierola et al, 2007), and the increased risk for obesity at this ADRB3 loci may be driven partly by an interaction effect of the PPARG SNP Pro12Ala Hsueh et al, 2001;Ochoa et al, 2004). Other studies in young children between the ages 4-10 years and in adolescents report no signifi cant effects of Trp64Arg variants on BMI, weight or height when this variant is examined in isolation (Cecil et al, 2007;Haworth et al, 2008a;Hinney et al, 1997;Kurokawa et al, 2003).…”
Section: Adrenergic Receptor Gene Variants -A Role In Polygenic Obesimentioning
confidence: 99%
“…In humans, the beta-3 adrenergic receptor is predominantly expressed in visceral adipose tissue (Krief et al, 1993). Notably, the Arg allele of this SNP has been linked with increased BMI, adiposity and obesity in children (Arashiro et al, 2003;Endo et al, 2000;Erhardt et al, 2005;Ochoa et al, 2004;Park et al, 2005) supporting the evidence in adults Pierola et al, 2007), and the increased risk for obesity at this ADRB3 loci may be driven partly by an interaction effect of the PPARG SNP Pro12Ala Hsueh et al, 2001;Ochoa et al, 2004). Other studies in young children between the ages 4-10 years and in adolescents report no signifi cant effects of Trp64Arg variants on BMI, weight or height when this variant is examined in isolation (Cecil et al, 2007;Haworth et al, 2008a;Hinney et al, 1997;Kurokawa et al, 2003).…”
Section: Adrenergic Receptor Gene Variants -A Role In Polygenic Obesimentioning
confidence: 99%
“…Japon çocuk-larda yapılan bir araştırmada da PPARG C161T varyasyonunun lipid metabolizması, leptin düzey-leri ve obezite ile ilişkili olduğu görülmüş ancak bu çocuklarda PPARG P12A varyantına rastlanmamıştır. 12 Bir başka çalışmada ise, KVH'si olan ve olmayan tip 2 diyabetiklerde PPARG P12A ve C161T varyasyonlarının yüksek BKİ değerleriyle ilişkili olmalarına rağmen KVH gelişimi üzerine etkilerinin olmadığı gözlenmiştir. 19 Buna karşılık, PPARG P12A ve C161T varyasyonları nefropatik diyabet hastalarındaki kardiyovasküler olaylar için belirteç olarak önerilmiş ve PPARG P12A minör Ala alleli ve C161T minör T alleli de kardiyovasküler risk artışından sorumlu olarak bildirilmiştir.…”
Section: Discussionunclassified
“…43 Bu örneklerde görüldüğü üzere, PPAR gen varyasyonlarının HDL-K ve LDL-K düzeylerine olan etkisi lipid metabolizmasıyla ilişkili metabolik ve kardiyovasküler sistem hastalıklarında pek çok toplumda çalışılmıştır. 12,19,[41][42][43] Buna karşılık, lipoprotein alt fraksiyonları üzerine etkisini araştı-ran sınırlı sayıda çalışma bulunmaktadır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In the coding region of this AR subtype a common missense mutation resulting in the substitution of arginine for tryptophan at codon 64 (Trp64Arg) has been reported to be significantly associated with whole body obesity, visceral fat accumulation and other metabolic syndrome components or their cluster [54][55][56][57]. Unfortunately, as previously observed in adults' studies, the association between Trp64Arg and BP levels in obese children was found significant in some studies [54,58] and not significant in others [51,53].…”
Section: α-And β-Adrenergic Receptors (Adra and Adrb) Genesmentioning
confidence: 95%